Design of a basigin-mimicking inhibitor targeting the malaria invasion protein RH5 - Warszawski,S; Dekel,E; Campeotto,J; Marshall,J; Wright,K; Lyth,O; Knop,N; Regev-Rudzki,N; Baum,J; Draper,S; Higgins,M; Fleishman,S (Proteins: Structure, Function, and Bioinformatics, 2020)
Many human pathogens use host cell-surface receptors to attach and invade cells. Often, thehost-pathogen interaction affinity is low, presenting opportunities to block invasion using asoluble, high-affinity mimic of the host protein. The Plasmodium falciparum reticulocyte-bindingprotein homolog 5 (RH5) provides an exciting candidate for mimicry: it is highly conserved andits moderate affinity binding to the human receptor basigin (KD≥1 μM) is an essential step inerythrocyte invasion by this malaria parasite. We used deep mutational scanning of a solublefragment of human basigin to systematically characterize point mutations that enhance basiginaffinity for RH5 and then used Rosetta to design a variant within the sequence space ofaffinity-enhancing mutations. The resulting seven-mutation design exhibited 2,500-fold higheraffinity (KD<1 nM) for RH5 with a very slow binding off rate (0.23 h-1) and reduced the effectivePlasmodium growth-inhibitory concentration by at least tenfold compared to human basigin. Thedesign provides a favorable starting point for engineering on-rate improvements that are likelyto be essential to reach therapeutically effective growth inhibition. Designed mimics may providetherapeutic advantages over antibodies, since the mimics bind to essential surfaces on the targetpathogen proteins, reducing the likelihood for the emergence of escape mutants